2017
DOI: 10.1038/ng.3757
|View full text |Cite
|
Sign up to set email alerts
|

Impaired H3K36 methylation defines a subset of head and neck squamous cell carcinomas

Abstract: Human papillomavirus negative (HPV-) head and neck squamous cell carcinomas (HNSCC) are deadly and common cancers. Recent genomic studies implicate multiple genetic pathways including cell-signalling, cell-cycle and/or immune evasion in their development. Here, we analyze public datasets and uncover a previously unappreciated role of epigenome deregulation in the genesis of 13% HPV-HNSCCs. Specifically, we identify novel recurrent p.K36M mutations occurring in multiple histone H3 genes. We further validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
216
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(228 citation statements)
references
References 48 publications
9
216
2
1
Order By: Relevance
“…Globally, our results show that HPV has a specific and genome-wide effect in shaping the DNA methylome of HNSCCs that is independent of other known major risk factors, such as tobacco smoking and alcohol consumption. Our results are similar to a recent report based on the analysis of the whole TCGA cohort [29]. The authors identified five subclusters of HNSSC based on DNA methylation patterns (528 samples), four HPV(–) clusters and one HPV(+) cluster [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Globally, our results show that HPV has a specific and genome-wide effect in shaping the DNA methylome of HNSCCs that is independent of other known major risk factors, such as tobacco smoking and alcohol consumption. Our results are similar to a recent report based on the analysis of the whole TCGA cohort [29]. The authors identified five subclusters of HNSSC based on DNA methylation patterns (528 samples), four HPV(–) clusters and one HPV(+) cluster [29].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to a recent report based on the analysis of the whole TCGA cohort [29]. The authors identified five subclusters of HNSSC based on DNA methylation patterns (528 samples), four HPV(–) clusters and one HPV(+) cluster [29]. …”
Section: Discussionsupporting
confidence: 90%
“…Among 28/51 genes significantly mutated and differentially distributed among the methylation clusters in SCC (Table S2L), hypermethylated HPV-enriched C2 also harbored fewer mutations in HRAS , CDKN2A(p16) , CASP8 , NFE2L2 , NSD1 , and TP53 than did clusters with predominantly HPV(−) SCC (Figures 4A and S3B). Strikingly, hypomethylation in C5 was linked to inactivating mutations in the H3K36 histone methyltransferase NSD1, defining a distinct subtype across SCC tissue sites previously observed in HNSC (Cancer Genome Atlas Network, 2015; Papillon-Cavanagh et al, 2017). …”
Section: Resultsmentioning
confidence: 72%
“…5, Supplementary Table 4), consistent with our previous report (Gevaert et al, 2015). Our NSD1-Smoking subtype corresponding to the H3K36me-impared subtype of HNSCC reported by Papillon-Cavanagh et al (2017). Thirty percent of patients within the CIMP-Atypical subtype featured CASP8 mutations, compared with 0–7% in other subtypes, a highly significant enrichment (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 73%